2023
DOI: 10.1051/e3sconf/202340504026
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of Wastewater through Implemented Wetland – A Review

Abstract: Contrary to the typical treatment system, built wetland systems have become high-performance wastewater treatment technology in recent years. In India as well, this technology is becoming more important for reducing water pollution. A built wetland is essentially a tank that has been planted with plants tolerant of waterlogged conditions and filled with a substrate. In this method, wastewater is treated by plants through phytoremediation. A manmade wetland's plant species is crucial in maintaining the temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Heavy metals will be degraded in plant tissue (Dixit et al 2015) or evaporates through the transpiration process into the atmosphere (Kumar et al 2023). Phytoremediation using the constructed wetlands method which utilises media and plants as a way to reduce pollutant levels is an alternative for dealing with environmental pollution (Metcalf 2003;Bilgaiyan 2023). Prasetya et al (2020) showed a decrease in mercury in the water media given by E. palifolius and zeolite in the SSF-CW (Subsurface-Constructed Wetlands) waste treatment system.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals will be degraded in plant tissue (Dixit et al 2015) or evaporates through the transpiration process into the atmosphere (Kumar et al 2023). Phytoremediation using the constructed wetlands method which utilises media and plants as a way to reduce pollutant levels is an alternative for dealing with environmental pollution (Metcalf 2003;Bilgaiyan 2023). Prasetya et al (2020) showed a decrease in mercury in the water media given by E. palifolius and zeolite in the SSF-CW (Subsurface-Constructed Wetlands) waste treatment system.…”
Section: Introductionmentioning
confidence: 99%